2021
DOI: 10.1302/0301-620x.103b7.bjj-2020-2414.r1
|View full text |Cite
|
Sign up to set email alerts
|

2021 John Charnley Award: A protocol-based strategy when using hemiarthroplasty or total hip arthroplasty for femoral neck fractures decreases mortality, length of stay, and complications

Abstract: Aims While interdisciplinary protocols and expedited surgical treatment improve the management of hip fractures in the elderly, the impact of such interventions on patients specifically undergoing arthroplasty for a femoral neck fracture is not clear. We sought to evaluate the efficacy of an interdisciplinary protocol for the management of patients with a femoral neck fracture who are treated with an arthroplasty. Methods In 2017, our institution introduced a standardized interdisciplinary hip fracture protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Possible explanations might be the selection of frail and high-risk patients to be treated by experienced surgeons, and the fact that patients treated with arthroplasty are preferentially operated on by more experienced surgeons and wait longer than other patients. 12 Orthogeriatric assessment is recommended to improve functional outcomes, 14 and has been shown to reduce mortality in FnFs receiving arthroplasty by roberts et al 22 in this study, orthogeriatric services were associated with lower mortality, all fracture types included. in a systematic review, abrahamsen et al 1 found that increased mortality might be elevated for years after injury, particularly for males.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Possible explanations might be the selection of frail and high-risk patients to be treated by experienced surgeons, and the fact that patients treated with arthroplasty are preferentially operated on by more experienced surgeons and wait longer than other patients. 12 Orthogeriatric assessment is recommended to improve functional outcomes, 14 and has been shown to reduce mortality in FnFs receiving arthroplasty by roberts et al 22 in this study, orthogeriatric services were associated with lower mortality, all fracture types included. in a systematic review, abrahamsen et al 1 found that increased mortality might be elevated for years after injury, particularly for males.…”
Section: Discussionmentioning
confidence: 56%
“…Orthogeriatric assessment is recommended to improve functional outcomes, 14 and has been shown to reduce mortality in FNFs receiving arthroplasty by Roberts et al 22 In this study, orthogeriatric services were associated with lower mortality, all fracture types included.…”
Section: Discussionmentioning
confidence: 61%
“…Finally, a retrospective study has reviewed the effectiveness of standardized interdisciplinary hip fracture protocol on, specifically, patients with femoral neck fractures treated with hemiarthroplasties (HA) or total hip arthroplasties (THA). A significantly decreased rate of major complication, decreased median length of hospital stay, decreased 1-year mortality, and increased rate of discharge home were observed amongst patients treated after the introduction of the protocol [ 36 ]. Despite the fact that subgroup analysis with accordance to fracture patterns or types of operated surgeries was not performed in this study, the protocol-driven treatment pathways might provide different extents of benefit to patient associated with certain fracture pattern or surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…CGA is not only for the disease itself but also for the overall situation of elderly patients [ 24 ] and not only pays attention to physical conditions but also pays more attention to cognitive and psychological conditions [ 25 , 26 ]. At present, the perioperative intervention effect of CGA on elderly hip fracture patients is not consistent, and there are very few studies on CGA in China [ 27 ]. For hip fracture patients over 65 years old, the implementation of CGA can reduce the mortality rate compared with the conventional group.…”
Section: Discussionmentioning
confidence: 99%